Traumatic stress and human DNA methylation: a critical review. (June 2015) - Vinkers, Christiaan H; Kalafateli, Aimilia Lydia; Rutten, Bart PF; Kas, Martien J; Kaminsky, Zachary; Turner, Jonathan D; Boks, Marco PM
Animal studies have identified persistent and functional effects of traumatic stress on the epigenome. This review discusses the clinical evidence for trauma-induced changes in DNA methylation across the life span in humans. Studies are reviewed based on reports of trauma exposure during the prenatal period (13 studies), early life (20 studies), and adulthood (ten studies). Even though it is apparent that traumatic stress influences the human epigenome, there are significant drawbacks in the existing human literature. These include a lack of longitudinal studies, methodological heterogeneity, selection of tissue type, and the influence of developmental stage and trauma type on methylation outcomes. These issues are discussed in order to present a way in which future studies can gain more insight into the functional relevance of trauma-related DNA methylation changes. Epigenetic studies investigating the detrimental effects of traumatic stress have great potential for an improved detection and treatment of trauma-related psychiatric disorders.